Respuesta :

Answer: Thanks!

Step-by-step explanation:

1 + 1

0 + 1 + 0 + 1

1 + 1

2

OR

a = b

(Step 1) Multiply both sides by b:

ab = b²

(Step 2) Subtract a² from both sides and factorize:

ab − a² = b² − a²

(Step 3)

a (b − a) = (b + a) (b − a)

(Step 4) Simplify and add 1 to both sides:

a = b + a

(Step 5)

a + 1 = b + a + 1

Now since a = b (the starting point of this proof), we can write this as:

a + 1 = 2a + 1

And in the case where a = 1, we have:

1 + 1 = 2 + 1

So, therefore,

1 + 1 = 3

OR

1 + 1 → 11 in binary

I'm sorry lol